Combined radiofrequency surgery of the tongue base and soft palate in obstructive sleep apnoea - Stuck, Boris; Starzak, Katrin; Hein, Gerhard; Verse, Thomas; Hörmann, Karl; Maurer, Joachim T. (Acta oto-laryngologica, 2004)
Objective To investigate the safety and efficacy of combined temperature-controlled radiofrequency volumetric tissue reduction of the tongue base and soft palate in obstructive sleep apnoea. Material and methods A total of 20 patients with obstructive sleep apnoea and combined palatal and retrolingual obstruction were included in a non-randomized clinical trial and 51 combined treatments were performed under local anaesthesia. Postoperative pain was assessed using visual analogue scales. Functional parameters, daytime sleepiness and quality of life were assessed using questionnaires (Epworth Sleepiness Scale, Short Form-36) before and 12 weeks after the last treatment session. Concurrently, polysomnography was performed on two consecutive nights. Results The mean postoperative pain score dropped from 5.6 at Day 1 to 0.6 at Day 7. Painkillers were taken for a mean of 3.3 days. There were no postoperative complications or changes in functional parameters. Daytime sleepiness improved significantly (p<0.05). The mean respiratory disturbance index was reduced from 25.3±11.4 to 16.7±15.3 (p<0.05). Six out of 18 (33%) patients were cured after a mean of 2.7 treatment sessions. Conclusion Combined radiofrequency volumetric tissue reduction of the tongue base and soft palate is a safe and effective treatment for obstructive sleep apnoea.